Cerebral blood flow characteristics of drug-naïve attention-deficit/hyperactivity disorder with social impairment: Evidence for region–symptom specificity - Zhang, Kangfuxi; Yuan, Jing; Pei, Xuyao; Fu, Zhao; Zhao, Yilu; Hu, Na; Wang, Yufeng; Yang, Li; Cao, Qingjiu (Frontiers in Neuroscience, 2023)
Background: Social deficit is among the most important functional impairments in Attention-deficit/hyperactivity disorder (ADHD). However, the relationship between social impairment and ADHD core symptoms as well as the underlying cerebral blood flow (CBF) characteristics remain unclear. Methods: A total of 62 ADHD with social deficits subjects (ADHD+SD), 100 ADHD without social deficits subjects (ADHD-SD) and 81 age-matched typically developing controls (TDC) were enrolled. We first examined the correlation between Social Responsiveness Scale (SRS-1) and the ADHD core symptoms and then explored categorical and dimensional ADHD-related regional CBF by arterial spin labeling (ASL). For the categorical analysis, a voxel-based comparison of CBF maps between ADHD+SD, ADHD-SD and TDC groups was performed. And for the dimensional analysis, the whole-brain voxel‐wise correlation between CBF and ADHD symptoms (inattention, hyperactivity/impulsivity, and total scores) was conducted in three groups. Finally, correlations between the SRS-1 and ADHD-related regional CBF were conducted. For all these imaging results, we applied Gaussian Random Field (GRF) for the correction of multiple comparisons, voxel-level P < .01, and cluster-level P < .05. Results: The clinical characteristics analysis showed that social deficits positively correlated with ADHD core symptoms, especially in social communication and autistic mannerisms domains. In categorical analysis, we found that the CBF in the left middle/inferior temporal was different between ADHD and TDC and was negatively correlated with social motivation score. Moreover, in dimensional analysis, we found that the CBF in the left middle frontal gyrus was negatively correlated to the inattention scores, SRS total score and autistic mannerisms score. Conclusion: The present study shows that inattention, hyperactivity and impulsivity may be responsible for the occurrence of social deficits for ADHD, with autistic traits being another significant contributing feature. Additionally, the CBF in the left middle/inferior temporal and the left middle frontal gyrus may be the corresponding physiological mechanisms underlying the social deficits in ADHD.